Subjective behavioral measures in myopic and pre-myopic children before and after the COVID lockdown - Alvarez-Peregrina, Cristina; Ruiz-Pomeda, Alicia; Martinez-Perez, Clara; Prieto-Garrido, Francisco Luis; Villa-Collar, Cesar; Gonzalez-Perez, Mariano; Gonzalez-Abad, Ana; Sanchez-Tena, Miguel Angel (Frontiers in Medicine, 2023)
Background: There are environmental factors that may contribute to the onset of myopia. This study aims to evaluate the children's lifestyle changes before and after the COVID-19 lockdown and how they can influence their vision. Methods: The same questionnaire was administered to children aged between 5 and 7 in Spain every year in September before (2017-2019) and after the COVID-19 lockdown (2020COVID-19 lockdown ( -2021)). All the children also passed a vision exam consisting of the measurement of visual acuity (VA) and determination of objective and subjective refraction. Children were classified as myopes, pre-myopes, or hyperopes. The cut-off points to define the refractive error were established according to the value of the spherical equivalent (SE): hyperopia (SE>+0,75D), myopia (SE≤-0,5D), or pre-myopia (-0.5D0.05). Regarding the spherical equivalent, in the pre-COVID period, the mean value was 0.75±2.09D and after the COVID lockdown, it was 0.47±1.88D (p<0.001). Conclusion: Premyopes spent more time outdoors than myopes in the pre-COVID period, while myopes spent more time using digital devices. All these differences do not exist after the COVID lockdown, with a general increase in the time spent outdoors and a decrease in the use of digital devices. Further studies are needed to know if these lifestyle changes remain and how they influence the onset of myopia.